Upaya Pemberdayaan Petani Bawang Merah Melalui Kebijakan Harga di Kabupaten Bantul Daerah Istimewa Yogyakarta - Siti Syamsiar (Economic Journal of Emerging Markets, 2007)
The purpose of this research is to analyze the role of onion price policy that is regulated by regional Government of Bantul regency, Yogyakarta Special Region Province. The Aim of policy is to improve the empowerment of onion farmer in this region. This Study was conducted using the simple random sampling to intake sample of population. The result showed that from 2002-2005 period, peak season of onion production is from April to May. During this period the production has been fluctuating with price range at Rp1.000,-/kg until Rp 1.800,-/kg. The government price policy is higher than the break event point price of onion in Bantul. It means that this policy in this region is effective to increase the onion price market, so that farmers can develop this farm, and finally it could improve the empowerment of onion farmer.Key words: empowerment, farmer, onion, price policy